Taking different routes – gender-atypical vocational education and training in the course of employment - Wagner, Pia [Verfasser]; Fournier, Lisa [Verfasser]; Dorau, Ralf [Verfasser] (My University, 2026)
"Gender-atypical VET could have the potential to reduce gender segregation on the labour market and to lessen gender-specific inequalities. Nevertheless, studies indicate poorer utilisation prospects of such training qualifications. In order to examine these more closely, this article identifies challenges people face in their later employment trajectory if they opted for training in an occupation dominated by the other gender. The basis is provided by interviews with people who have left their gender-atypical training occupation and on expert interviews." (BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; G 2.4.5 Gender Mainstreaming; 370; Berufsausbildung; Männerberuf; Frauenberuf; Qualifikationsverwertung; Geschlechtersegregation; Berufswechsel; Interview